Profile of the Older Population Living in Miami-Dade County, Florida: An Observational Study - Zevallos, Juan C. (Medicine (Baltimore), 2016)
Florida has the greatest proportion (19%) of older population (65 years or older) in the United States. The age distribution of its residents, in conjunction with a major shift in the leading cause of death within all age groups from acute illnesses to chronic disease, creates unprecedented health care challenges for the state. The objective of this study is to profile the older population living in Miami-Dade County (MDC) using 3 population-based, household-based surveys conducted over the past 5 years. This study examined cross-sectional data (demographics, health outcomes, risk factors, health assess, and utilization) collected from probability-sampled, household-based surveys conducted in 3 areas of MDC: north Miami-Dade, Little Haiti, and South Miami. The questionnaire was administered face-to-face by trained interviewers in English, Spanish, French, or Creole. Analyses were restricted to households containing at least 1 member aged 65 years or older (n = 935). One consenting adult answered the questionnaire on behalf of household members. The mean age of the respondent (60% females) was 60 years. Overall, respondents were predominantly African-Americans, Hispanics, and blacks of Haitian origin. One-third of all households fell below the US poverty thresholds. One-quarter of all households had at least 1 member who was uninsured within the year before the survey. Twenty percent of households had at least 1 member with an acute myocardial infarction or stroke during the year before the survey. Bone density tests and blood stool tests were strikingly underutilized. The health outcomes most prevalent within household members were cardiovascular diseases followed by cancer, anxiety/depression, obesity, asthma, and bone fractures. Twenty percent of households reported having at least 1 current smoker. Overall, emergency rooms were the most commonly used places of care after doctor's offices. Findings of 3 household-based surveys show a predominantly elderly, female, uninsured, and poor minority populations living in MDC, FL. The reported use of preventive services was constrained, and emergency room use was often reported as a main resource for health care. Cardiovascular disease, cancer, bone fractures, and related risk factors were the most prevalent health outcomes.